TRANSITING TO VIRTUAL LEARNING UNDER THE NEW NORMAL: PROSPECTS AND CHALLENGES FOR NIGERIAN UNIVERSITIES: A STUDY OF OLABISI ONABANJO UNIVERSITY, OGUN STATE - Olanipekun Lateef Okikiola (American Journals, 2022)
COVID-19 pandemic has changed the way of learning in higher education. Teaching, and learning activities that are usually carried out with face-to-face meetings have turned into virtual meetings in various online learning applications. This paper aims to analyze student essays in the form of perspectives or responses about the challenges of online learning in Olabisi Onabanjo University. Online learning provides various instructions led by the lecturer. Instructions can be synchronous (communication where participants interact in the same time space as video conferencing, zoom, Google meet, and WebEx) or asynchronous (time-separated communication such as e-mail, Google form, streaming video content, posting lecture notes and social media platforms). This paper has shown so many responses about the challenges experienced by the students while studying online, such as, positive and negative impact of online learning, economic conditions, anxiety during online learning, and management of Olabisi Onabanjo University should think and plan for the risk of user data security, and find effective means towards enhancing online learning media towards meeting students’ expectations.
Keywords: Online Learning; Transition; Traditional learning